Highly Stable Indium‐Gallium‐Zinc‐Oxide Thin‐Film Transistors on Deformable Softening Polymer Substrates. (22nd August 2017) - Gutierrez‐Heredia, Gerardo; Rodriguez‐Lopez, Ovidio; Garcia‐Sandoval, Aldo; Voit, Walter E.
Abstract: Flexible electronics are attracting great interest in healthcare, where devices such as thin‐film transistors (TFTs) on polymer substrates facilitate biomedical applications requiring complex circuits in soft packages. Consequently, a repeatable process to fabricate reliable, stable electronic components on flexible substrates is required. Here, thermoset thiol‐ene/acrylate shape memory polymer (SMP) substrates house indium‐gallium‐zinc‐oxide (IGZO) TFTs and logic circuits: resulting devices exhibit stable behavior after thermal annealing at 250 °C. Fabricated, annealed devices exhibit an average mobility of 15 ± 2.5 cm 2 V −1 s −1 and show stability after bending and soaking in aqueous media. TFTs on SMPs are studied after mechanical bending tests with radii of curvature of 5 mm for 10 4 cycles over a 4 h time period. Other TFTs are soaked in phosphate‐buffered saline solution at 37 °C for 1 week. Logic inverter circuits using IGZO TFTs on SMPs represent the ability to add complex circuitry onto thin film flexible electronics. This technology can enable a new generation of implantable devices for research in healthcare fields. Abstract : Flexible thin‐film transistors (TFTs) using an oxide semiconductor and a high‐k dielectric are fabricated on top of softening substrate. These substrates are also known as shape‐memory polymers because they have the capacity to return to their original shape after deformation into a metastable shape. The TFTs exhibit mobility values of 15 cm 2 V −1 s −1 and electrical stability after bending and soaking in aqueous media.